Proposal for the design of a digital marketing plan for the growth of the Dental Service dental office in Guayaquil - Albuja Sánchez, Julio Alejandro; Soriano Echeverría, María Del Pilar; Indio Choez, Katty Naila (Ingeniería Química y Desarrollo, 2024)
The present research work has been directed with the aim of demonstrating in the viable by means of a Digital Marketing Plan for the company Dental Service S.A which is a center of dentistry and aesthetics in this way we want to make known the business has that impulse to have that impulse to stand out in the market through social networks that are of great importance today for the recruitment of customers who want to take care of their image so it was also decided to create a website on Wix a free platform with its paid version where it is provided the use of it for entrepreneurs who require the use of know their services and prices Inside the document we will observe the marketing methods that were used to develop the thesis project where they were located
Keywords: Digital Marketing; Digital Tools; Advertising; Social Networks; Websites